A New Strategy for Surgical Intervention of Bisphosphonate-Related Osteonecrosis of the Jaw : A retrospective study - Rokutanda, Satoshi; Uda, Akiko; Yanamoto, Souichi; Kakehashi, Hiroe; Umeda, Masahiro; Yamada, Shin-ichi; Hayashida, Saki; Naruse, Tomofumi; Asahina, Izumi; Matsusita, Yuki; Ikeda, Hisazumi (Acta Medica Nagasakiensia, 2016)
Bisphosphonates (BPs) are now widely used to treat various skeletal complications. Although the number of reported cases ofbisphosphonate-related osteonecrosis of the jaw (BRONJ) is rapidly increasing worldwide, therapeutic strategies remain controversial.Conservative treatments including antibacterial mouth rinses, the systemic administration of antibiotics, and superficialdebridement in stage II BRONJ have been recommended by the American Association of Oral and Maxillofacial Surgeons positionpaper. However, these treatments are only partially successful. We performed a surgical intervention that consisted of osteotomyand primary wound closure in patients with stages II and III BRONJ. Forty-three out of 44 cases were treated effectivelyby this strategy, leading to improvements in quality of life. All BRONJ patients treated with oral BPs were treatedsuccessfully by the surgical intervention. We also proposed a surgical intervention for patients with stage II BRONJ.